ANALISIS BALAGHAH TERHADAP HADIS NIAT DALAM ARBA'IN NAWAWI: KAJIAN STRUKTUR BAHASA DAN IMPLIKASI TEOLOGIS - Ramdani Nopandri; Mely Rahmadani; Nizar Ali (DIRAYAH : Jurnal Ilmu Hadis, 2026)
This study examines the rhetorical dimensions (balaghah ) of the first hadith in Imam al-Nawawi's Arba'in, namely the hadith on intention (niyyah) "Innama al-a'malu bi al-niyyat." Using a descriptive-analytical method grounded in a linguistic and theological approach, this research analyzes the stylistic features of the hadith text, including its syntactic structure (nahwu), lexical choices (bayan), and the rhetorical devices embedded therein (badi'). Drawing on recent scholarship in Arabic rhetoric, the study finds that the use of the particle "innama" as a tool of restriction (qasr) plays a central role in conferring exclusive meaning upon intention, while the plural form "a'mal" signals the universality of the ruling. The hadith's rhetorical compactness (jawami' al-kalim) is consistent with prophetic eloquence. Theologically, these rhetorical choices underpin the Islamic jurisprudential principle that deeds are validated solely by intention, with profound implications for Islamic ethics, worship, and legal theory (usul al-fiqh). This study contributes to the development of hadith linguistic studies and enriches the discourse on the intersection of Arabic rhetoric and Islamic theology.